2003
DOI: 10.1046/j.1365-294x.2003.01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term temporal changes of genetic composition in brown trout (Salmo truttaL.) populations inhabiting an unstable environment

Abstract: The genetic structure of brown trout (Salmo trutta) populations inhabiting rivers on the island of Bornholm in the Baltic Sea was studied on a spatial and temporal scale. Low water levels in the rivers during the summer period are assumed to have a significant impact on the persistence of local populations, possibly resulting in a metapopulation structure. Extinctions may, however, also be buffered by a remnant strategy, whereby juveniles escape to river outlets during periods of drought. We compared polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
127
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 48 publications
13
127
1
2
Order By: Relevance
“…Consequences of gene flow: Our study adds to a growing number of empirical investigations of N e in salmonid fish (e.g., Østergaard et al 2003;Shrimpton and Heath 2003;Lage and Kornfield 2006;Fraser et al 2007b;Vähä et al 2008). Using various temporal genetic methods, we document relatively high estimates of N e as well as increases inN e in small populations over time.…”
Section: Discussionmentioning
confidence: 80%
“…Consequences of gene flow: Our study adds to a growing number of empirical investigations of N e in salmonid fish (e.g., Østergaard et al 2003;Shrimpton and Heath 2003;Lage and Kornfield 2006;Fraser et al 2007b;Vähä et al 2008). Using various temporal genetic methods, we document relatively high estimates of N e as well as increases inN e in small populations over time.…”
Section: Discussionmentioning
confidence: 80%
“…H e , A and F temporal for five time periods from 1944 to 1997 [40]. It was found that H e and A were high and stable over time, but that F temporal varied substantially among periods.…”
Section: Monitoring Recruitment In Wild Populationsmentioning
confidence: 94%
“…However, several recent studies in systems with volatile environmental conditions, where metapopulation dynamics may be more likely, have suggested contrasting dynamics. Temporal instability in allele frequencies in steelhead (Oncorhynchus mykiss) and brown trout has been attributed to changes in connectivity and population structure caused by channel-blocking landslides (Heath et al 2002) and extreme spatiotemporal fluctuations in stream flow and habitat conditions (Ostergaard et al 2003). Extremely low effective population sizes and severe bottlenecks observed in Lahontan cutthroat trout suggest that some populations fluctuate in size and may be vulnerable to extirpation.…”
Section: E T a P O P U L A T I O N D Y N A M I C S A N D C O Nn E Cmentioning
confidence: 99%